Software architecture : the hard parts : modern trade-off analysis for distributed architectures - Ford, Neal; Richards, Mark (W. Mark); Sadalage, Pramod J.; Dehghani, Zhamak (Ascent Audio, 2023)
There are no easy decisions in software architecture. Instead, there are many hard parts-difficult problems or issues with no best practices-that force you to choose among various compromises. With this book, you'll learn how to think critically about the trade-offs involved with distributed architectures. Architecture veterans and practicing consultants Neal Ford, Mark Richards, Pramod Sadalage, and Zhamak Dehghani discuss strategies for choosing an appropriate architecture. By interweaving a story about a fictional group of technology professionals, they examine everything from how to determine service granularity, manage workflows and orchestration, manage and decouple contracts, and manage distributed transactions to how to optimize operational characteristics, such as scalability, elasticity, and performance. This book provides techniques to help you discover and weigh the trade-offs as you confront the issues you face as an architect. You'll find out how to analyze trade-offs and effectively document your decisions; make better decisions regarding service granularity; understand the complexities of breaking apart monolithic applications; manage and decouple contracts between services; handle data in a highly distributed architecture; and learn patterns to manage workflow and transactions when breaking apart applications.